Diamine Derivatives as Photostabilizers for Thermoplasticized Poly(Vinyl Chloride) [I] (Baghdad Science Journal, 2018)
The photostabilization? of poly vinyl chloride (PVC) ? films has been investigated by using diamine derivatives. The? (PVC) films were? contained 0.5% weight? of diamine derivatives which prepared by the method of casting. The photostabilizations? ?of these compounds were determined by monitoring the carbonyl index value with irradiation time. Also, the effect ?of concentrations of additives (range 0.1-0.5wt) on the rate of photostabilization? process was studied. Therefore we found? that a increased photostabilization rates was increase with increasing? concentrations of compound. Besides, the influence? on film thickness? of photostabilization process was also studied; ?and the results? showed that? the increasing of film thickness increase the rate of photostabilization. Also, the changes in the viscosity? of the averagee molecular weight, the degree? of deterioration (?) and the average number of chain scission (s) were tracked, it was concluded? that the random chain scission is always occurs in PVC film, also Quantum yield? of the chain? scission of? these compounds? was calculated. Several mechanisms? have been? suggested and according to experimental results obtained, these mechanisms are dependent on the structure? of? the additive, Among UV absorper? and radical? scavenger.